El derecho de alimentos y la responsabilidad estatal a la luz del derecho comparado - Jines Vaca, Pamela Fernanda (2025)
The scientific article examines state responsibility for the guarantee of food rights in the context of comparative law, focusing on Ecuadorian legislation and its similarities with other jurisdictions. The Ecuadorian legal framework, which prioritizes the rights of children and adolescents, establishes the state obligation to ensure their integral development, including access to food. The International Convention on the Rights of the Child and the Organic Code of Children and Adolescents reinforce this principle, recognizing the best interests of the child as a fundamental element in decision-making. Therefore, based on comparative law, the role of the State as a subsidiary obligation in the setting of alimony is analyzed, highlighting state intervention as crucial to protect the rights of children in vulnerable situations. The methodology used is qualitative and not experimental, using an analytical-synthetic and inductive-deductive approach to compare national and international regulations. A documentary analysis and surveys will be carried out to a focus group related to children and adolescents to obtain relevant information on the research topic. This study is expected to provide a critical analysis of state regulation in the guarantee of food rights and how it can improve to protect the rights of children and adolescents more effectively in Ecuador. In addition, it seeks to compare these policies with other legislations to identify best practices and possible areas for improvement in Ecuadorian legislation.